An Application of Shari’ah Law In Curbing Corruption In Contemporary Nigeria - Saliu Yisa (Penerbit Hellow Pustaka, 2026)
Over the years, corruption has been the bane of development in Nigeria. This menace has eaten deep into all sectors in the country. Through, corruption has always been a serious problem in most developing countries most especially in AFRICA, Nigeria is not an exception. Nigeria, corruption has eaten deep into education, healthy, judiciary, political leaders among others. The paper adopted historical and sociological research approaches for data gathering and analysis. The paper discovered that, even religion houses are left out in terms of corruption. It was also unfolded that unemployment, lack of transparency, fear of poverty and greed are among the major factors that enhance and encourage corruption in Nigeria. Though, many governments in the country have put one measure or another in place to fight corruption, but it seems the measure put in place has not yielded much result, as many political office holders are still found carting away millions and billions of Naira on yearly basis. The paper therefore recommended stiffer punishment for anybody found carting away public funds in Nigeria.